Baseline blood pressure, low- and high-density lipoproteins, and triglycerides and the risk of vascular events in the stroke prevention by aggressive reduction in cholesterol levels (SPARCL) trial - Amarenco, Pierre; Goldstein, Larry B.; Callahan, Alfred; Sillesen, Henrik; Hennerici, Michael G.; O’Neill, Blair J.; Rudolph, Amy E.; Simunovic, Lisa; Zivin, Justin A.; Welch, K. M. A. (Atherosclerosis, 2009)
Objective - To explore the relative contributions of baseline systolic blood pressure (SBP) and diastolic blood pressure (DBP) and lipoproteins on the risk of recurrent stroke or first major cardiovascular event (MCVE) and their potential impact on the benefit of statin treatment. - Methods and results - The SPARCL trial randomized 4731 patients with recent stroke or transient ischemic attack (TIA) and no known coronary heart disease and LDL-C between 100 and 190mg/dL to either atorvastatin 80mg/d or placebo. Baseline assessment included SBP, DBP and measurements of low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C), and triglyceride levels. After 4.9 years of follow-up, there were 575 primary end points (fatal and nonfatal stroke), including 491 ischemic strokes, and 740 MCVEs (stroke plus myocardial infarction and vascular death). Cox regression models analysis showed a trend (P>0.05 and P<0.10) for higher SBP but not DBP to be associated with an outcome stroke with only SBP associated with MCVE. Only baseline low HDL-C was associated with an outcome stroke. Baseline HDL-C, triglycerides, and LDL/HDL ratio were each associated with MCVEs. There were no interactions between any of these baseline variables and the effect of treatment on outcome strokes. - Conclusions - In patients with recent stroke or TIA and no coronary heart disease, only lower baseline HDL-C predicted the risk of recurrent stroke with HDL-C, triglycerides, and LDL/HDL ratio associated with MCVE. Atorvastatin treatment was similarly effective regardless of baseline lipoprotein levels.
Available online 18 September 2008
Gesehen am 17.03.2021